How duration and frequency influence horticultural therapy’s effect on depressive symptoms: evidence from a meta-analysis - Chen, Lin; Sun, Youlong; Pan, Yidian; Chen, Ruqi; Liu, Chang (Frontiers in Psychology, 2025)
BackgroundHorticultural therapy (HT) has been documented to significantly intervene in depressive symptoms, but the effect of temporal characteristics is unclear.Methods11 databases were searched updated by 12th October 2024. 33 studies were included through quality assessment. A standardized mean difference (SMD) employing a random-effects model was used to assess the effect size of HT intervention for depressive symptoms, and the effect size was compared for different frequency, duration, session duration subgroups.ResultsOverall, HT interventions for depressive symptoms were effective (SMD = −0.95). For intervention frequency, less than 3 times weekly (SMD = −1.21) was superior to 3 and more times weekly. For intervention duration, 5–8 weeks (SMD = −1.75) was superior to shorter (≤ 4 weeks) and longer (≥ 9 weeks) programs. For session duration, more than 60 min (SMD = −1.35) was superior to shorter ones. Optimal effects may emerge when implementing less than 3 HT sessions weekly, each lasting over 60 min, for a duration of 5–8 weeks.ConclusionThis study revealed the influence of temporal characteristics on the effectiveness of HT intervention for depressive symptoms. Since most of the included studies were conducted in Asia, the conclusions can better guide HT practices for Asian cultural groups.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024523923, CRD42024523923.